1996
DOI: 10.1002/(sici)1097-4628(19961205)62:10<1551::aid-app7>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Syndiotacticity-rich poly(vinyl alcohol) fibers spun fromN-methylmorpholine-N-oxide/water mixture

Abstract: Aqueous NMMO solutions containing NMMO above 50% are good solvents for syndiotacticity‐rich poly(vinyl alcohol) (s‐PVA). Although water is not a good solvent and dissolves s‐PVA at temperatures above 100°C, the mixtures dissolve it at temperatures below 100°C. s‐PVA fibers were prepared through gel‐spinning of s‐PVA/NMMO/water (NMMO: water = 70 : 30) mixtures in cold water and wet‐spinning of the solution in methanol. The mechanical properties and fine structure of the drawn fibers were examined based on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many studies have attempted to increase the strength of PVA fibers, including syndiotactic poly­(vinyl alcohol) (PVA with alternating stereochemistry). However, researchers have reported that orientation by advanced stretching is difficult for syndiotactic PVA because strong hydrogen bonds between PVA molecules inhibit high molecular orientation . Also, with the development of gel spinning and other methods, high-strength PVA fibers are available in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to increase the strength of PVA fibers, including syndiotactic poly­(vinyl alcohol) (PVA with alternating stereochemistry). However, researchers have reported that orientation by advanced stretching is difficult for syndiotactic PVA because strong hydrogen bonds between PVA molecules inhibit high molecular orientation . Also, with the development of gel spinning and other methods, high-strength PVA fibers are available in the market.…”
Section: Introductionmentioning
confidence: 99%